Prevalence and Determinants of Depression Among Multi Drug Resistant (MDR) TB Cases - Muhammad Ayub, Aliya Khan, Darshana Kumari, Saifullah, Zile Huma, Muhammad Saqib Habib (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: We aimed this study to find the prevalence of depression among multi drug resistant (MDR) TB patients and its related determinants. Material and methods: An observational cross-sectional study was conducted at Jinnah Postgraduate Medical Center Karachi hospital, we enrolled 107 MDR-TB patients using non-probability consecutive sampling. Patients were evaluated for depression using Patient Health Questionnaire-9 (PHQ-9). Prevalence of depression along with its determinant were assessed. We used Chi Square test for association between depression and its determinants keeping P value < 0.05 was taken as statistically significant. Results: Patients’ mean age was 32.10±6.19, male patients were higher in number as compared to female patients. In our study we found that depression was present in 52 (48.6%) patients. Depression had significant association with financial issues, family problems, treatment duration and increasing age. Practical implication: Current study assess the determinants of depression in TB patients and spreads public awareness in community about Multidrug resistance in TB and ways to avoid TB in local population. Conclusion: From our study we conclude that 52 (48.6%) patients had depression in MDR-TB patients which is an alarming situation. Financial issues, family problems, treatment duration and increasing age were found to the determinants of depression in MDR-TB patients. Keywords: Tuberculosis, Multi Drug Resistance, Depression, Truenat, Xpert, Mental disorders, psychiatric comorbidity